Hop production - Rybacek, Vaclav (Developments in crop science, 1991)
This book deals in detail with all aspects of hop growing, hop cone handling, drying, storage and processing into hop products and preparations, and with their utilization in the brewing industry. Particular attention is given to theoretical and practical hop production problems from the perspective of biology, chemistry, and economics, the ultimate objective of the book being high-quality hop raw materials for the brewing industries. The book is intended for hop growers, traders, brewing specialists, agricultural colleges, hop research and brewing industry institutes.